Role of inflammation and immunity in vascular calcification: a bibliometric and visual analysis, 2000–2022 - Wang, Chen; Liang, Qingchun; He, Siyi; Zhu, Jie; Lin, Xiafei; Lin, Guanwen; Wu, Duozhi; Zhang, Wenqi; Wang, Zhihua (Frontiers in Cardiovascular Medicine, 2023)
Background In recent years, a great deal of research has been done on vascular calcification (VC), and inflammation and immunity have been displayed to play important roles in the mechanism of VC. However, to date, no comprehensive or systematic bibliometric analyses have been conducted on this topic. Methods Articles and reviews on the roles of inflammation and immunity in VC were obtained from the Web of Science Core Collection on August 5, 2022. Four scientometric software packages—HistCite, CiteSpace, VOSviewer, and R-bibliometrix—were used for the bibliometric and knowledge mapping analyses. Results The obtained 1,868 papers were published in 627 academic journals by 9,595 authors of 2,217 institutions from 69 countries. The annual number of publications showed a clear growth trend. The USA and China were the most productive countries. Karolinska Institutet, Harvard University, and the University of Washington were the most active institutions. Stenvinkel P published the most articles, whereas Demer LL received the most citations. Atherosclerosis published the most papers, while Circulation was the most highly cited journal. The largest cluster among the 22 clusters, based on the analysis of co-citations, was osteo-/chondrogenic transdifferentiation. “Vascular calcification,” “inflammation,” “chronic kidney disease,” and “expression” were the main keywords in the field. The keyword “extracellular vesicle” attracted great attention in recent years with the strongest citation burst. Conclusions Osteo-/chondrogenic transdifferentiation is the primary research topic in this field. Extracellular vesicles are expected to become a new research focus for exploring the inflammatory and immune mechanisms of VC.